2019
DOI: 10.1017/s0954579418001487
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver–adolescent co-reminiscing and adolescents’ individual recollections of a devastating tornado: Associations with enduring posttraumatic stress symptoms

Abstract: Although disaster-related posttraumatic stress symptoms (PTSS) typically decrease in intensity over time, some youth continue to report elevated levels of PTSS many years after the disaster. The current study examines two processes that may help to explain the link between disaster exposure and enduring PTSS: caregiver emotion socialization and youth recollection qualities. One hundred and twenty-two youth (ages 12 to 17) and their female caregivers who experienced an EF-4 tornado co-reminisced about the event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…A more recent, mixed-methods examination of communication demonstrates its role in understanding lingering distress post-disaster. Hendrickson et al (2019) had parents and children age 12-17 years engage in a co-reminiscing task about their experiences during a deadly tornado. They found that a parent communication style where the caregiver focused the conversation on their own emotions, perceptions, and experiences, at the expense of their child's ability to share, was significantly related to PTSS assessed years post-disaster.…”
Section: Family Communication In the Post-disaster Contextmentioning
confidence: 99%
“…A more recent, mixed-methods examination of communication demonstrates its role in understanding lingering distress post-disaster. Hendrickson et al (2019) had parents and children age 12-17 years engage in a co-reminiscing task about their experiences during a deadly tornado. They found that a parent communication style where the caregiver focused the conversation on their own emotions, perceptions, and experiences, at the expense of their child's ability to share, was significantly related to PTSS assessed years post-disaster.…”
Section: Family Communication In the Post-disaster Contextmentioning
confidence: 99%
“…Relatedly, a conflict event could be too innocuous to induce the level of emotional intensity and types of reminiscing qualities that may implicated in the development of youth rumination and depression. For example, in a parent-adolescent reminiscing study investigating the development of adolescent PTSS symptoms after a traumatic event, parent egocentrism (i.e., parent self-focused orientation) during parent-adolescent reminiscing about the traumatic event was related to adolescent experiences of greater PTSS symptoms (Hendrickson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…in development across childhood and beyond. Robust findings show that children's engagement in reminiscing conversations with their caregivers improves their autobiographical memory and narrative skill, their ability to understand and manage their emotions, and other skills that lay the foundations for psychological wellbeing (Fivush, Haden, & Reese, 2006;Hendrickson, Abel, Vernberg, McDonald, & Lochman, 2019;Salmon & Reese, 2016).…”
Section: Conversations Between Parents and Children About Past Experiences Play A Crucial Rolementioning
confidence: 93%
See 2 more Smart Citations